Human Blood Grup and Rhesus Detection Tool Prototype Design Based On IoT - Hendrawati, Trisiani Dewi; Hasanudin, Inzaghi (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
Currently, medical practitioners carry out blood type and rhesus examinations by directly observing the agglutination reaction and depending on the examiner's eye. Meanwhile, the effects of eye fatigue and saturation will cause inaccurate data. Therefore, a detection device was made which aims to display information about reading human blood type and rhesus on a digital display which can also store the data into a database. The ABO and rhesus systems were used in this study. This research was made using a real-time method based on the internet of things (IoT). sending data in real-time using WiFi Module ESP-01 and other components such as LCD microcontroller, LDR, LED, battery, and Arduino Uno. based on the results of tool testing, the percentage of success values is 91.67%.